Induction of CD4 T cell memory responses following BCG vaccination in cattle - Sterle, Haley M.; Putz, Ellie J.; Olsen, Steven C.; Boggiatto, Paola M. (Frontiers in Veterinary Science, 2024)
Mycobacterium bovis, the causative agent of bovine tuberculosis (bTB), is a zoonotic pathogen that contributes to economic losses in the cattle industry and poses a public health risk worldwide. Bacillus Calmette-Guerin, or BCG, is a live attenuated strain of M. bovis that is used for human vaccination against tuberculosis and is considered a potential vaccine candidate against bTB. However, BCG affords widely variable levels of protection against challenge and interferes with current diagnostic methods, and as such, it is not currently approved for use as a livestock or wildlife vaccine in the United States. Many efforts have been made to develop bTB vaccines that are reliable and do not interfere with diagnostic testing, but BCG continues to be the most effective option. Previous work has shown that a T helper 1 immune response is essential for protection against virulent M. bovis infection, characterized by CD4+ central and effector memory T cells. In an effort to identify an efficacious bTB intervention strategy, the study presented here used an in vitro recall response assay and concurrent evaluation of CD4+ T cell proliferation and cytokine production to characterize the surface and functional phenotypes of memory responses to BCG vaccination in cattle. Our findings enhance understanding of the bovine immune response to BCG and provide insights into the development of improved vaccines for the control of bTB.